Size and Structural Effect of Crumpled Graphene Balls on the Electrochemical Properties for Supercapacitor Application. (20th December 2016) - Jo, Eun Hee; Choi, Ji-Hyuk; Park, Su-Ryeon; Lee, Chong Min; Chang, Hankwon; Jang, Hee Dong
Abstract: Effect of size and structure of a three-dimensional (3D) crumpled graphene balls (CGBs) on the electrochemical performance was investigated for supercapacitor application. Different sized CGBs were firstly fabricated by one-step aerosol spray pyrolysis. Electrochemical performance of 3D CGBs for supercapacitor was then measured with respect to size and structural characteristics. The average size of CGBs was controlled in a range of 0.3 to 0.7 μm. CGBs were composed of a few tens of 2D graphene sheets, resulting in different porous structures. CGBs exhibited higher specific surface area and smaller pore volume, and they are composed of micro- and mesopores. The electrochemical performance of supercapacitors fabricated with the as-prepared CGBs, having a different morphology and pore structure, was then evaluated. The maximum specific capacitance of 156 F/g was obtained when 0.7 μm CGBs were employed. In that case, the highest specific energy density and power density were approximately 22 Wh/kg and 4 kW/kg, respectively.